Low-complexity likelihood probability derivation algorithm for non-binary LDPC-coded modulation system - Guang-hua HE; Bao-ming BAI; Xiao MA; Bing LI (Tongxin xuebao, 2013)
The derivation of likelihood probabilities which are sent into the decoder in many LDPC-coded modulation systems is a challenging task especially when high-order modulations are used.This is because likelihood probabilities are usually complicated functions of the channel output and their calculation also requires knowledge of the channel parameters.To this end,a low-complexity likelihood probability derivation algorithm was proposed.Also,the Euclidean distance between the received signal and the constellation points was considered to divide the constellation points into two signal sets.Simulation results show that the proposed algorithm provides good trade-offs between performance and complexity,making it a good candidate for the hardware implementation of the front-end in the non-binary LDPC decoders.